Outlawed : A Novel - North, Anna (New York : Bloomsbury Publishing, 2021)
The Crucible meets True Grit in this riveting adventure story of a fugitive girl, a mysterious gang of robbers, and their dangerous mission to transform the Wild West.
Keywords: Outlaws -- Fiction; Outcasts -- Fiction; Midwives -- Fiction; Infertility -- Fiction; Pregnancy -- Fiction -- Social aspects; Influenza -- Fiction; Epidemics -- Fiction; Paranormal fiction; West (U.S.) -- Fiction; Action and adventure fiction; Western fiction